The Relationship Between Psychological Well-Being and Bullying Among Junior High School Students - Nabiela Nurkhaliza Rahmany; Gian Sugiana Sugara; Anandha Putri Rahimsyah (Journal of Mental Health and Well-Being in Counseling, 2026)
Psychological well-being is one of the essential indicators in adolescent mental development, which determines their ability to function adaptively within social environments, particularly at school. This study aims to analyze the description of psychological well-being and the correlation between psychological well-being and bullying among junior high school students who are victims of bullying. This research employed a quantitative approach with a descriptive correlational design, involving 209 students of SMPN 6 Tasikmalaya selected using purposive sampling. The instruments used included the Adolescent Peer Relations Instrument (APRI) to measure bullying and the Brief Scale of Psychological Well-Being for Adolescents (BSPWB-A) to measure psychological well-being. The findings indicated that among 71 students identified as bullying victims, the majority fell into the moderate category of psychological well-being (69.0%), followed by 21.1% in the low category and 9.9% in the high category. Correlation analysis revealed a negative relationship between psychological well-being and bullying, meaning that the higher the students’ psychological well-being, the lower the level of bullying experienced. The dimension of positive relation with others demonstrated the strongest negative correlation, whereas autonomy was the lowest-scoring dimension among bullying victims. These findings emphasize the importance of emotional support–based interventions and school counseling services to strengthen students’ psychological well-being, thus minimizing the impact of bullying.